Evaluating heavy metals emission' pattern on road influenced by urban road layout. (June 2021) - Pal, Sudip K.; Roy, Roman
Highlights: Heavy metal sediment concentrations at different road sites addressing urban road layout. Summary statistics of heavy metal concentrations in RDS and TLS. A greater number of stronger associations of heavy metal with TLS than with RDS. Heavy metal emission patterns are influenced by site-specific factors and traffic movement pattern. Abstract: Road traffic sector comprises a small percentage of urban land uses while acts as a sink of pollutants among which heavy metals such as, Zn, Cu, Cd, Cr, Ni, Pb are often found in elevated concentrations influenced by urban road layout in addition to traffic volumes and are found hazardous due to their persistent and low degradation nature. This study aims to evaluate heavy metals of Zn, Cu, Ni and Pb in road deposited sediment (RDS) and tree leaf sediment (TLS) influenced by typical urban road layout taking a road section in Chittagong city, Bangladesh. The RDS and TLS at different sites were collected using dry sweeping and then were air dried in a controlled environment at the laboratory. The samples were then sieved through 75 µm size. The selected heavy metal concentrations in RDS and TLS were determined using ICE spectrophotometer followed by strong nitric acid digestion. The different statistical analyses, e.g., correlation analysis, Kruskal-Wallis and Mann-Whitney tests were carried out to explore the source appointment, interdependences, significant differences in metal concentrations among the selected sites. The mean concentrations of the heavy metals are found in the order of Zn > Cu > Pb > Ni with their magnitude of 160, 36, 30 and 11.5 mg kg−1, respectively, across the site and sampling types. The RDS and TLS are found substantially enriched, having enrichment factor range 1.13 to 1.83 than their respective background values indicating anthropogenic input in the samples illustrating emission from the road traffic environment. In general, the higher metal concentrations are found in TLS than in RDS with considerable variability exist among the sites. Considering the heavy metal induced pollution level, the sites rank is in the order of controlled intersection > road bend > road with speed control > uncontrolled intersection > straight road section > bus stop > uncontrolled intersection with flyover site. These results highlighting site specific characteristics notably with traffic volume and traffic movement pattern influenced by stop-start phenomenon linked to a typical urban road lay out design. The statistical analyses further confirm the findings of interrelationships with the significant variability across the samples and sites.